(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Acacia liquid honey can be processed into powdered honey using vacuum drying. The aim of this research is to obtain optimal conditions for powdered honey formulation consisting of the percentage of liquid honey and operational conditions, namely drying temperature. To obtain this, chemical tests are carried out, namely reducing sugar, diastase enzyme, and IC50. This research uses the Design Expert 12 application with the RSM (Response Surface Method) method, namely CCD (Central Composite Design) with 2 factors and 3 responses. The results of processing powdered honey obtained optimal results at a liquid honey percentage of 70% compared to maltodextrin of 30% and a drying temperature of 55oC. Chemical testing obtained optimal results for reducing sugar of 68%, diastase enzyme of 3.35, and IC50 of 18.88 mg/ml.